THE RELATIONSHIP OF AGE OF PREGNANT WOMEN TO WOMEN'S KNOWLEDGE ABOUT THE BIRTH PLANNING AND COMPLICATIONS PREVENTION PROGRAM (P4K) - Aprilia Peni Yukisara; Rita Yulifah; Duhita Diah Apsari (SEAJOM: The Southeast Asia Journal of Midwifery, 2023)
Pregnancy, childbirth, childbirth and newborns are physiological conditions. This condition can suddenly experience life-threatening complications for the mother and baby. Monitoring the health of pregnant women and preparation for childbirth can be done through the P4K program. P4K is a birth planning and complication prevention program that aims to reduce complications in pregnancy/delivery. The purpose of this study was to analyze the relationship between the age of pregnant women and P4K knowledge. Analytic descriptive research design with a cross sectional approach. the research sample is 51 respondents. Data collection instrument using a questionnaire. Results: 51% of mothers are aged 26-35 years. most mothers have good knowledge about P4K. The results of the analysis of the Spearman Test for age and knowledge of P4K obtained a P-value of 0.000. This shows that the older the mother, the better her knowledge about P4K